IMMUNE EPITOPE CONTINUUM OF THE PROTEIN RELATIONSHIPS, POLY- AND AUTOREACTIVITY OF ANTIBODIES - E. P. Kharchenko (Медицинская иммунология, 2015)
Computer analysis of primary structure for >3300 proteins has shown an opportunity for existence of global immune epitope continuum of protein relationships (IECPR) for eukaryotes, prokaryotes, and viruses. On the basis of IECPR, one may provide new interpretations for immune events, and in particular, to consider them as an additional factor determining poly- and autoreactivity of antibodies, and, respectively, extend the concept of regulatory functions of natural antibodies. For medical practice, the IECPR would be especially useful in cases of search for novel vaccines and immune diagnostic preparations.